A Case of Ruptured Decidualized Ovarian Endometrioma: Usefulness of Serial MRI for Determining Adequate Management - Saki Yamamoto; Tomohiro Kikuchi; Hiroyuki Fujii; Yuko Otake; Mitsuru Matsuki; Risa Narumi; Masashi Endo; Hiroyuki Fujiwara; Harushi Mori (Case Reports in Obstetrics and Gynecology)
Decidualization can originate in ovarian endometrioma by elevated serum progesterone levels during pregnancy, which mimics malignancy on ultrasonography. Moreover, decidualized ovarian endometrioma may rupture and cause acute abdominal pain during pregnancy. Magnetic resonance imaging (MRI) is reportedly useful in differentiating decidualized ovarian endometriomas from malignancies. However, to our knowledge, serial MRI of decidualized ovarian endometrioma before and after rupture has not been reported. Herein, we report the case of a 39-year-old woman with a ruptured decidualized ovarian endometrioma in which serial MRI was useful for adequate management. She had a history of right ovarian endometrioma. Transvaginal ultrasonography at 20 weeks of gestation showed the known right ovarian endometrioma with mural nodules that were not evident before pregnancy. MRI for further evaluation showed ovarian endometrioma with mural nodules with signals similar to those of the placenta. Based on the MRI findings, we diagnosed a decidualized ovarian endometrioma. At 27 weeks of gestation, she complained of sudden abdominal pain, for which MRI was performed. MRI showed disappearance of the ovarian endometrioma and bloody ascites, based on which we diagnosed a ruptured ovarian endometrioma. The abdominal pain subsided immediately, and a conservative observational treatment approach was taken. At 37 weeks of gestation, right ovarian cystectomy was performed simultaneously with an elective cesarean section, which revealed a ruptured decidualized ovarian endometrioma. Our findings demonstrate that the accurate diagnosis of a ruptured decidualized ovarian endometrioma on serial MRI can contribute to its management.